Magnesium increases insulin-dependent glucose uptake in adipocytes - Oost, Lynette J.; Kurstjens, Steef; Ma, Chao; Hoenderop, Joost G. J.; Tack, Cees J.; de Baaij, Jeroen H. F. (Frontiers in Endocrinology, 2022)
Background Type 2 diabetes (T2D) is characterized by a decreased insulin sensitivity. Magnesium (Mg2+) deficiency is common in people with T2D. However, the molecular consequences of low Mg2+ levels on insulin sensitivity and glucose handling have not been determined in adipocytes. The aim of this study is to determine the role of Mg2+ in the insulin-dependent glucose uptake. Methods First, the association of low plasma Mg2+ with markers of insulin resistance was assessed in a cohort of 395 people with T2D. Secondly, the molecular role of Mg2+ in insulin-dependent glucose uptake was studied by incubating 3T3-L1 adipocytes with 0 or 1 mmol/L Mg2+ for 24 hours followed by insulin stimulation. Radioactive-glucose labelling, enzymatic assays, immunocytochemistry and live microscopy imaging were used to analyze the insulin receptor phosphoinositide 3-kinases/Akt pathway. Energy metabolism was assessed by the Seahorse Extracellular Flux Analyzer. Results In people with T2D, plasma Mg2+ concentration was inversely associated with markers of insulin resistance; i.e., the lower Mg2+, the more insulin resistant. In Mg2+-deficient adipocytes, insulin-dependent glucose uptake was decreased by approximately 50% compared to control Mg2+condition. Insulin receptor phosphorylation Tyr1150/1151 and PIP3 mass were not decreased in Mg2+-deficient adipocytes. Live imaging microscopy of adipocytes transduced with an Akt sensor (FoxO1-Clover) demonstrated that FoxO1 translocation from the nucleus to the cytosol was reduced, indicting less Akt activation in Mg2+-deficient adipocytes. Immunocytochemistry using a Lectin membrane marker and at the membrane located Myc epitope-tagged glucose transporter 4 (GLUT4) demonstrated that GLUT4 translocation was diminished in insulin-stimulated Mg2+-deficient adipocytes compared to control conditions. Energy metabolism in Mg2+ deficient adipocytes was characterized by decreased glycolysis, upon insulin stimulation. Conclusions Mg2+ is essential for normal insulin-dependent glucose uptake in adipocytes and suggests that Mg2+ deficiency may contribute to insulin resistance in people with T2D.